Were there any missing mediators between visual impairment and anxiety symptoms? Results from Chinese Longitudinal Healthy Longevity Survey - Yao, Wen; Cao, Yuan; Tian, Yuan; Liu, Yuanyuan; Hua, Xin; Chen, Fang (Frontiers in Public Health, 2024)
Introduction Visual impairment, encompassing low visual acuity and visual field loss, significantly impacts the older adult population worldwide, leading to increased disability and mortality risks. Recent studies suggest a strong association between visual impairment and anxiety, particularly among older adults. This study aims to explore the relationship between visual impairment and anxiety symptoms in older adult individuals in China, and to investigate potential mediating factors. Methods Data for this study were derived from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS), including 11,702 participants aged 65 and older. Visual impairment was assessed through self-reported visual function, while anxiety symptoms were measured using the 7-item Generalized Anxiety Disorder scale (GAD-7). Additional assessments included sleep quality and duration, exercise status, and dietary diversity. Logistic regression models and mediation analysis were employed to explore associations and mediating effects. Results The findings indicate that visual impairment is significantly associated with increased anxiety symptoms among the older adult (OR = 1.51, 95% CI: 1.32–1.72, p < 0.001). Mediation analysis revealed that sleep quality, dietary diversity score (DDS), and plant-based DDS significantly mediated the relationship between visual impairment and anxiety. In contrast, sleep duration, exercise, and animal-based DDS did not show significant mediating effects. Conclusion Visual impairment is a crucial predictor of anxiety symptoms in the older adult. Improving sleep quality and promoting a diverse plant-based diet may mitigate anxiety symptoms in this population. Interventions targeting these areas could enhance the mental health and quality of life of older adult individuals with visual impairment.